The right to be forgotten regarding genetic data: A legal and ethical analysis - Correia, Mónica; Rego, Guilhermina; Nunes, Rui (Acta Bioethica, 2024)
This article investigates an under-discussed provision of the European Union’s (EU’s) General Data Protection Regulation (GDPR) regarding genetic data, i.e., the right to be forgotten. The debate on this right came from the commerce-related side of data protection instead of the medical side. Thus, this article addresses the implications of the RTBF for the lawful processing of familial genetic data. The article develops a normative, ethically focused principles argument about interpreting genetic data’s right to be forgotten. It gives due consideration to autonomy, privacy, and human dignity. It argues that the individualistic approach of genetic privacy materialised through the extreme solution of data erasure is challenging to combine with familial and scientific research interests. The article suggests an interpretation of the GDPR according to bioethical principles and the inclusion of a specific exception regarding genetic data to prevent patients from claiming the right to be forgotten. Keywords: bioethics, data protection, genetic data, privacy, right to be forgotten.